IMC9 Edinburgh Nomenclature Sessions - L.L. Norvell; D.L. Hawksworth; R.H. Petersen; S.A. Redhead (IMA Fungus)
The proceedings of the 3-5 August 2010, IMC9 Edinburgh Nomenclature Sessions are briefly summarized. The final resolution approved by the General Assembly endorses the recommendations by the Nomenclature Sessions regarding transfer of the governance of fungal nomenclature from botanical to mycological congresses, mandatory pre-publication deposit of nomenclatural information for valid publication of new fungal names, and the acceptability of English as an alternative to Latin in the valid publication of fungal names. Complete results from the IMC9 nomenclature questionnaire are also provided.